Pengaruh Strategi Critical Incident Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di Kelas X IPA SMA Swasta Universitas Islam Sumatera Utara Tahun Pelajaran 2020/2021 Medan Kota - Husaini, Ahmad (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
Critical incident (important experience), a strategy to activate students since the start of learning, students must remember and describe their past experiences in accordance with the topic of the material presented ". With this strategy students are directly involved actively and are able to increase the interaction between students and educators. As it is known that this interaction is in the form of feedback from students, this feedback can be in the form of concentration, asking opinions, asking and answering questions and arousing discussion. This study aims to determine the effect of the critical incident strategy on student learning outcomes in Islamic religious education subjects. This research was conducted at UISU Private High School, North Sumatra. The population in this study were 192 students of class X IPA at UISU Private High School for the academic year 2020/2021 which consisted of six classes, the sampling technique used in this study was purposive sampling. The subjects in this study were students of class X IPA which consisted of 32 people, namely 15 boys and 17 girls. The research method used was experimental. Meanwhile, the data used in this research are quantitative data. The instruments used were tests both pretest and posttest, observation and interviews. Data analysis techniques to test the hypothesis in this study using the t test. Based on the results of calculations with 70 degrees of freedom, obtained tcount = 10.98 and ttable = 1.66. The results of these calculations show that tcount ≥ ttable (10.98 ≥ 1.66). So it can be concluded that there is an effect of the use of critical incident active learning strategies on student learning outcomes in the subject of Islamic Religious Education in class X IPA Private High School, Islamic University of North Sumatra.